Sistem Pendidikan Inklusif Perspektif Neurosains - Novianti, Ely (Al-Misbah (Jurnal Islamic Studies), 2020)
Assesing inclusion education in neuroscience perspectives is particularly interesting. This study is a literature review. Given the development of normal and special needs children have different backgrounds. Cognitive development of children are different according to parenting patterns. In this case the parents need to be aware of the type of child and need to understand in terms of neuroscience. Keep in mind education is the right of every child to gain knowledge and educate the individual. The background of every child is not an obstacle in getting a decent education. The government and education authorities now have acces to the concept of inclusive education. With the application of inclusive education can expand access to education for all groups including children with disabilities. This effort is made to develop the potential of intelligence, talent,and soft skills prossessed without discrimination.in addition, at the age of gold, children with special needs are directed to interest and talent. With experience early on hope when adolescents are able to hone and can compete with normal children. This is because there is already a maturity in the individual’s ability and creativity.